Could Gameplay Data of Games with a Purpose Assist in Training Hazardous Situations in the Industry? - Cristiano Barroso Serra; Tadeu Moreira de Classe (Journal on Interactive Systems, 2024)
Accidents and risks in the industry pose significant challenges concerning executing critical tasks. Inadequate employee training compromises the ability to manage risks, making the environment prone to accidents. In this context, games with training purposes emerge as a promising solution, providing an interactive and immersive environment. Focusing on improved risk management, organizational managers can utilize data collected by these games as metrics for monitoring and enhancement. However, it is necessary to understand how games with a purpose can contribute to the training process for hazardous situations in the industry. With this in mind, this study investigates the topic by exploring both the literature through a systematic mapping and the perceptions of workers from an oil and gas industry through a survey. As a result of the investigations, techniques for analyzing and visualizing gameplay data obtained from training games, design elements, game genres, and primary usage contexts were identified. Additionally, it was possible to analyze workers' perceptions from the oil and gas industry of how these games and their data can add value and contribute to safety training sections within their workplaces. Therefore, there were indications that games with a purpose, combined with data analysis and visualization techniques, can offer a new perspective for conducting and evaluating training, providing information that contributes to improving work quality indices and reducing severe accident risks within the industry.